2016
DOI: 10.1142/s0218271816500231
|View full text |Cite
|
Sign up to set email alerts
|

Genericity aspects of black hole formation in the collapse of spherically symmetric slightly inhomogeneous perfect fluids

Abstract: We study the complete gravitational collapse of a class of spherically symmetric inhomogeneous perfect fluid models obtained by introducing small radial perturbations in an otherwise homogeneous matter cloud. Our aim here is to study the genericity and stability of the formation of black holes and locally naked singularities in collapse. While the occurrence of naked singularities is known for many models of collapse, the key issue now in focus is genericity and stability of these outcomes. Towards this purpos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…When a collapsing matter cloud virializes before the formation of a black hole, then the above mentioned spacetime structure can be formed. There are many literature where the final state of collapsing matter cloud is discussed elaborately [16,[37][38][39][40][41][42][43]. In [44], it is shown that Bertrand spacetimes (BST) can be formed as an equilibrium state of gravitational collapse.…”
Section: Timelike Geodesics In Schwarzschild and Bst Spacetimesmentioning
confidence: 99%
“…When a collapsing matter cloud virializes before the formation of a black hole, then the above mentioned spacetime structure can be formed. There are many literature where the final state of collapsing matter cloud is discussed elaborately [16,[37][38][39][40][41][42][43]. In [44], it is shown that Bertrand spacetimes (BST) can be formed as an equilibrium state of gravitational collapse.…”
Section: Timelike Geodesics In Schwarzschild and Bst Spacetimesmentioning
confidence: 99%
“…For example, a spherical homogeneous collapse would create a Schwarzschild black hole, which has an event horizon and a singularity at the center. A physically more realistic class of collapse models, with non-zero pressures and inhomogeneities in the matter distribution included were studied in [39][40][41]. The final outcome of the collapse asymptotically then was obtained as an equilibrium configuration, with a singularity at the center, but with no event horizon, as trapped surfaces fail to form as the collapse proceeds.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that there is always a possibility that singularity becomes globally and locally visible, at least for some time. The genericity of these naked singularities was also investigated [54], [55] [56], and it was found that there can be generic naked singularity solutions of Einstein equation. This does not really disprove the CCC, as there is always a debate on the physical viability of the initial conditions which are taken for a collapsing scenario.…”
Section: Stellar Collapse and Cosmic Censorship Conjecturementioning
confidence: 99%